Memahami Basa Walikan dalam Membentuk Identitas Komunitas Masyarakat Kampung Badran, Yogyakarta - Gusti Purbo Darpitojati; Turnomo Rahardjo (Interaksi Online, 2019)
This study aims to describe the process of identity forming in society’s community of Kampung Badran, Yogyakarta by basa walikan. This study is a qualitative study using naturalistic paradigm and phenomenological approach. The data in this study is obtained by doing in-depth interviews with five informants who are natives of Kampung Badran, in the age range of 35-60 years old and owning experiences related to using basa walikan in interactions among their community’s members. The results of this study are the process of identity forming begins with using basa walikan in interactions that occur in society’s community of Kampung Badran, both inside and outside the kampung. The usage of the language inside the kampung triggered other people in that community’s curiosity who then asked to be taught how to speak in that language, and then that language is spread inside society’s community in Kampung Badran. When the speakers were interacting using basa walikan outside Kampung Badran, many people in the outside of Kampung Badran became curious dan wanted to learn about that language, and then the speakers taught them how to use basa walikan. Due to basa walikan being taught to people outside Kampung Badran, that language became spread dan spoken extensively in youth’s intercommuncation in Yogyakarta. The using of basa walikan brings up certain identities that the speakers want to show, such as being “unique” and “different from the others”. Identities are also pinned by others to the language and the speakers based on their knowledge and experience, such as “thug”, “thug’s language”, and “unique”. Along with the degradation of basa walikan’s speakers, the living speakers choose to integrate themselves into the group of dominant cultural identity.